2007
DOI: 10.1089/thy.2007.0185
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Graves' Ophthalmopathy: The Role of Autoantibodies

Abstract: The clinical manifestations of Graves' ophthalmopathy (GO) stem from a combination of increased orbital fat and extraocular muscle volume within the orbital space. Fibroblasts residing within these tissues are thought to be targets of autoimmune attack in the disease. Thyrotropin receptor (TSHr) mRNA and functional protein have been demonstrated in orbital fibroblasts from both normal individuals and GO patients, with higher levels present in the latter. Autoantibodies directed against TSHr or the insulin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
96
0
12

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 43 publications
1
96
0
12
Order By: Relevance
“…The GO ocular manifestations include eyelid retraction, proptosis, chemosis, periorbital edema, altered ocular motility, and loss of vision with significant functional, social, and cosmetic consequences. [1][2][3][4] As there are few clues currently available to assist clinicians in estimating GO prognosis, it is very difficult to predict which patients will suffer from such severe sequelae. Recently, Eckstein et al 5 reported that persistently high TSH-receptor antibody (TRAb) levels were associated with a severe course of GO by demonstrating that TRAb levels at 12-24 months after diagnosis were significantly higher in patients with a severe course of GO than in those with a mild outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The GO ocular manifestations include eyelid retraction, proptosis, chemosis, periorbital edema, altered ocular motility, and loss of vision with significant functional, social, and cosmetic consequences. [1][2][3][4] As there are few clues currently available to assist clinicians in estimating GO prognosis, it is very difficult to predict which patients will suffer from such severe sequelae. Recently, Eckstein et al 5 reported that persistently high TSH-receptor antibody (TRAb) levels were associated with a severe course of GO by demonstrating that TRAb levels at 12-24 months after diagnosis were significantly higher in patients with a severe course of GO than in those with a mild outcome.…”
Section: Introductionmentioning
confidence: 99%
“…TSHR antibodies act as TSH agonists and induce thyroid overactivity. It has been estimated that 25%-50% of GD patients have clinical signs of Graves' ophthalmopathy or orbitopathy (GO), with the vast majority having relatively mild disease (3,4). As with all autoimmune disorders, it is thought that GD is caused by the interaction of genetic, epigenetic, and environmental factors in a stochastic manner.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite recent progress in the understanding of its pathogenesis, clear and indisputable mechanisms have not been established and treatment is often not satisfactory. [4][5][6][7][8][9] It may represent a complex interplay among orbital fibroblasts, immune cells, cytokines, autoantibodies, genetics, and environmental factors. [9][10][11][12][13] Recently, there is growing evidence that a change of reactive oxygen species (ROS) metabolism has been implicated in the aetiopathogenesis of several autoimmune disorders including Graves' disease and GO.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] It may represent a complex interplay among orbital fibroblasts, immune cells, cytokines, autoantibodies, genetics, and environmental factors. [9][10][11][12][13] Recently, there is growing evidence that a change of reactive oxygen species (ROS) metabolism has been implicated in the aetiopathogenesis of several autoimmune disorders including Graves' disease and GO. [14][15][16] Bednarek et al 17,18 reported that the ROS and antioxidant enzymes were increased in peripheral blood of hyperthyroid patients and euthyroid patients with infiltrative ophthalmopathy.…”
Section: Introductionmentioning
confidence: 99%